2016
DOI: 10.1111/phn.12248
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Immigrant Parents about Food and Feeding Practices: Public Health Nurses' Experiences

Abstract: Counseling immigrant parents on food and feeding at CHCs is often challenging for PHNs. The study findings could be used in the development of guidelines to assist PHNs in delivering culturally competent counseling about food and feeding practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
(34 reference statements)
2
17
0
Order By: Relevance
“…In order to customise advice about food and feeding to the family situation, factors related to the parents are key components and thus to be taken into account. Nevertheless, findings from a previous study reveal that health personnel in a preventive healthcare setting disclose that they rarely ask about aspects such as food preferences of the family or the family situation in attempting to adjust their counselling about food and feeding practices (Holmberg Fagerlund, Pettersen, Terragni, & Glavin, ). By omitting these significant details in a healthcare setting, one might cause the parents to turn to advice from friends or relatives or even to perceive social pressure about when they should start giving solid foods to their infant.…”
Section: Discussionmentioning
confidence: 99%
“…In order to customise advice about food and feeding to the family situation, factors related to the parents are key components and thus to be taken into account. Nevertheless, findings from a previous study reveal that health personnel in a preventive healthcare setting disclose that they rarely ask about aspects such as food preferences of the family or the family situation in attempting to adjust their counselling about food and feeding practices (Holmberg Fagerlund, Pettersen, Terragni, & Glavin, ). By omitting these significant details in a healthcare setting, one might cause the parents to turn to advice from friends or relatives or even to perceive social pressure about when they should start giving solid foods to their infant.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing inequalities in health status is a key aim of public health nursing (Edgecombe & World Health Organization, ). A typical task in public health nursing is counselling parents about food and feeding issues related to their infants (Redsell et al, ) and children below school age (Hemingway, Aarts, Koskinen, Campbell, & Chasse, ; Holmberg Fagerlund, Pettersen, Terragni, & Glavin, ; Ilmonen, Isolauri, & Laitinen, ). The child health centre (CHC) is frequently the context for public health nurses’ (PHNs’) counselling parents with under school‐aged children (Bramhagen, Axelsson, & Hallström, ; Holmberg Fagerlund et al, ; Ilmonen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings of a recent study focusing on the experiences of PHNs indicated that PHNs possessed limited strategies and tools for addressing nutritional issues at the CHC, particularly adapted to clients’ cultural diversity (Holmberg Fagerlund et al, ). This prompted a need for additional training on client counselling strategies as well as culturally appropriate information materials and visual aids to assist PHNs in delivering equitable services at the CHCs (Holmberg Fagerlund et al, ). This was therefore seen as a rationale for preparing a communication tool about diet for universal use in PHN consultations at the CHC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations